Sdha+/- Rats Display Minimal Muscle Pathology Without Significant Behavioral or Biochemical Abnormalities. Issue 8 (8th May 2018) - Siebers, Emily M; Choi, Melinda J; Tinklenberg, Jennifer A; Beatka, Margaret J; Ayres, Samuel; Meng, Hui; Helbling, Daniel C; Takizawa, Akiko; Bennett, Brian; Garces, Alexander M; Dias Duarte Machado, Luiz-Gabriel; Dimmock, David; et al.
Abstract: Mitochondrial diseases (MDs) result from alteration of the mitochondrial respiratory chain (MRC) function. Despite the prevalence of MDs in the population, the paucity of animal models available limits the understanding of these disorders. Mutations in SDHA, a gene that codes for the alpha subunit of succinate dehydrogenase (SDH), can cause some forms of MD. SDHA is a crucial contributor to MRC function. In order to expand the range of MD animal models available, we attempted to generate a Sdha knockout rat. Since homozygous Sdha -/- rats could neither be identified in newborn litters, nor as early as embryonic day 14, we evaluated wild-type (WT) and heterozygous Sdha + /- genotypes. No differences in behavioral, biochemical, or molecular evaluations were observed between WT and Sdha +/- rats at 6 weeks or 6 months of age. However, 30% of Sdha +/- rats displayed mild muscle fiber atrophy with rare fibers negative for cytochrome oxidase and SDH on histochemical staining. Collectively, our data provide additional evidence that modeling SDH mutations in rodents may be challenging due to animal viability, and heterozygous rats are insufficiently symptomatic at a phenotypic and molecular level to be of significant use in the study of SDH deficiency.